Scribal punctuation of coordinate and subordinate clauses in Late Middle English and Early Modern English - Esteban-Segura, María Laura; Calle-Martín, Javier (My University, 2018)
The study of punctuation has traditionally focused on Old and Middle English handwritten material—literary and scientific texts in particular, while the early modern period has been left unexplored (Calle-Martín forthcoming). The existing approaches to the topic are, however, descriptions of the system of individual texts, which offer a detailed analysis of the choices and preferences of particular scribes. The diachronic approach has been frequently disregarded, perhaps on the erroneous assumption that punctuation lacks uniformity. The present paper, therefore, sets to analyse scribal punctuation from a diachronic perspective in late Middle and early Modern English in order to shed some new light on the standardisation of punctuation symbols in the expression of three types of clauses: coordinate clauses, adjectival clauses (defining and non-defining relative clauses) and conditional if-clauses. The study relies on handwritten material from The Málaga Corpus of Early English Scientific Prose for the historical period 1300–1700. The corpus has been compiled to contain both theoretical treatises and recipe material written in the 15th, 16th and 17th centuries, which allows for a diachronic and variationist approach to the study of punctuation.
Keywords: Inglés - Puntuación